Subcellular transcriptomics—Dissection of the mRNA composition in the axonal compartment of sensory neurons. Issue 3 (18th November 2013) - Minis, Adi; Dahary, Dvir; Manor, Ohad; Leshkowitz, Dena; Pilpel, Yitzhak; Yaron, Avraham; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT RNA localization is a regulatory mechanism that is conserved from bacteria to mammals. Yet, little is known about the mechanism and the logic that govern the distribution of RNA transcripts within the cell. Here, we present a novel organ culture system, which enables the isolation of RNA specifically from NGF dependent re‐growing peripheral axons of mouse embryo, sensory neurons. In combination with massive parallel sequencing technology, we determine the subcellular localization of most transcripts in the transcriptome. We found that the axon is enriched in mRNAs that encode secreted proteins, transcription factors, and the translation machinery. In contrast, the axon was largely depleted from mRNAs encoding transmembrane proteins, a particularly interesting finding, since many of these gene products are specifically expressed in the tip of the axon at the protein level. Comparison of the mitochondrial mRNAs encoded in the nucleus with those encoded in the mitochondria, uncovered completely different localization pattern, with the latter much enriched in the axon fraction. This discovery is intriguing since the protein products encoded by the nuclear and mitochondrial genome form large co‐complexes. Finally, focusing on alternative splice variants that are specific to axonal fractions, we find short sequence motifs that are enriched in the axonal transcriptome. Together our findings shed light on the extensive role of RNA localization and its characteristics. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 365–381, 2014